Depositional ages and characteristics of Middle–Upper Jurassic and Lower Cretaceous lacustrine deposits in southeastern Mongolia. (27th February 2018) - Hasegawa, Hitoshi; Ando, Hisao; Hasebe, Noriko; Ichinnorov, Niiden; Ohta, Tohru; Hasegawa, Takashi; Yamamoto, Masanobu; Li, Gang; Erdenetsogt, Bat‐Orshikh; Heimhofer, Ulrich; Murata, Takayuki; Shinya, Hironori; et al.
Abstract: Lower Cretaceous lacustrine oil shales are widely distributed in southeastern Mongolia. Due to the high organic carbon content of oil shale, many geochemical studies and petroleum exploration have been conducted. Although most of the oil shales are considered to be Early Cretaceous in age, a recent study reveals that some were deposited in the Middle Jurassic. The present study aims at establishing depositional ages and characteristics of the Jurassic and Cretaceous lacustrine deposits in Mongolia. The Lower Cretaceous Shinekhudag Formation is about 250 m thick and composed of alternating beds of shale and dolomite. The Middle Jurassic Eedemt Formation is about 150 m thick and composed of alternating beds of shale, dolomitic marl, and siltstone. The alternations of shale and dolomite in both formations were formed by lake level changes, reflecting precipitation changes. Shales were deposited in the center of a deep lake during highstand, while dolomites were formed by primary precipitation during lowstand. Based on the radiometric age dating, the Shinekhudag Formation was deposited between 123.8 ±2.0 Ma and 118.5 ±0.9 Ma of the early Aptian. The Eedemt Formation was deposited at around 165–158 Ma of Callovian–Oxfordian. The calculated sedimentation rate of the Shinekhudag Formation is between 4.7 ±2.6 cm/ky and 10.0 ±7.6 cm/ky. Shales in the Shinekhudag Formation show micrometer‐scale lamination, consisting of algal organic matter and detrital clay mineral couplets. Given the average thickness of micro‐laminae and calculated sedimentation rate, the micro‐lamination is most likely of varve origin. Both Middle–Upper Jurassic and Lower Cretaceous lacustrine oil shales were deposited in intracontinental basins in the paleo‐Asian continent. Tectonic processes and basin evolution basically controlled the deposition of these oil shales. In addition, enhanced precipitation under humid climate during the early Aptian and the Callovian–Oxfordian was another key factor inducing the widespread oil shale deposition in Mongolia. Abstract : The present study aims at establishing depositional ages and characteristics of the Jurassic and Cretaceous lacustrine deposits in Mongolia. Based on radiometric age dating, the Shinekhudag Formation was deposited between 123.8 ±2.0 Ma and 118.5 ±0.9 Ma of early Aptian, and the Eedemt Formation was deposited at around 165–158 Ma of Callovian–Oxfordian. Although basin tectonics may have affected the deposition of these lacustrine oil shales, enhanced precipitation within a humid climatic setting during the early Aptian and the Callovian–Oxfordian times is more likely to be a key factor of the widespread occurrence of lacustrine environments in southeast Mongolia.